Недостатки, причины их возникновения и противоречия развития известных физических принципов действия упругих элементов систем подрессоривания военных гусеничных и колесных машин - Дущенко, Владислав Васильевич (НТУ "ХПИ", 2007)
By functional, technological, economic and anthropological criteria of development the analysis of physical principles of action of elastic elements of systems of a cushioning military caterpillar and wheel machines in which basis Guk law and gas laws lay is carried out. The basic lacks of these physical principles of action, the reason of their occurrence and the contradiction of development are revealed. It is shown, that at the present stage of development, a major factor in maintenance of quantitative values of parameters of quality which demand improvement, necessity at each moment of time is to operate rigidity of elastic elements of a uspension bracket.
Keywords: эволюция технических систем; физические принципы действия; технические решения; упругие элементы; пнемвмогидравлическая рессора; ТР-торсион